Fibrous nanocellulose, crystalline nanocellulose, carbon nanotubes, and crocidolite asbestos elicit disparate immune responses upon pharyngeal aspiration in mice. (1st January 2018) - Park, Eun-Jung; Khaliullin, Timur O.; Shurin, Michael R.; Kisin, Elena R.; Yanamala, Naveena; Fadeel, Bengt; Chang, Jaerak; Shvedova, Anna A.
Abstract: With the rapid development of synthetic alternatives to mineral fibers, their possible effects on the environment and human health have become recognized as important issues worldwide. This study investigated effects of four fibrous materials, i.e. nanofibrillar/nanocrystalline celluloses (NCF and CNC), single-walled carbon nanotubes (CNTs), and crocidolite asbestos (ASB), on pulmonary inflammation and immune responses found in the lungs, as well as the effects on spleen and peripheral blood immune cell subsets. BALB/c mice were given NCF, CNC, CNT, and ASB on Day 1 by oropharyngeal aspiration. At 14 days post-exposure, the animals were evaluated. Total cell number, mononuclear phagocytes, polymorphonuclear leukocytes, lymphocytes, and LDH levels were significantly increased in ASB and CNT-exposed mice. Expression of cytokines and chemokines in bronchoalveolar lavage (BAL) was quite different in mice exposed to four particle types, as well as expression of antigen presentation-related surface proteins on BAL cells. The results revealed that pulmonary exposure to fibrous materials led to discrete local immune cell polarization patterns with a TH 2-like response caused by ASB and TH 1-like immune reaction to NCF, while CNT and CNC caused non-classical or non-uniform responses. These alterations in immune response following pulmonary exposure should be taken into account when testing the applicability of new nanosized materials with fibrous morphology.